2018
DOI: 10.1088/1361-6552/aadbc7
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the teaching of elementary particle physics

Abstract: Elementary particle physics is gradually implemented into science curricula at high school level. However, common presentations on educational, semitechnical or popular level contain or support severe misconceptions. We discuss in particular the notion of "particle", the interaction between them and the use of Feynman diagrams. In many cases the true novelty of particle physics (i.e. quantum field theory) is largely ignored. We also suggest reasons for this widespread distortions of particle physics in popular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
0
8
0
3
Order By: Relevance
“…For example, spectral lines can be-and frequently are-explained with a planetary Bohr model of the atom [60]. Likewise, several authors point out that the presentation of the photoelectric effect in many textbooks is oversimplified and might not enhance students' understanding of QP [61][62][63][64]. However, the popularity of these items supports the findings of Kragh, who already in 1992 found that "Virtually all textbooks introduce the quantum postulate-that is, the necessity of conceiving physical processes as discontinuous at the atomic or subatomic level-by referring to a number of experimental facts that were discovered in the early part of the twentieth century and which seem inexplicable without the hypothesis of quantization."…”
Section: (Quasi-)historymentioning
confidence: 99%
“…For example, spectral lines can be-and frequently are-explained with a planetary Bohr model of the atom [60]. Likewise, several authors point out that the presentation of the photoelectric effect in many textbooks is oversimplified and might not enhance students' understanding of QP [61][62][63][64]. However, the popularity of these items supports the findings of Kragh, who already in 1992 found that "Virtually all textbooks introduce the quantum postulate-that is, the necessity of conceiving physical processes as discontinuous at the atomic or subatomic level-by referring to a number of experimental facts that were discovered in the early part of the twentieth century and which seem inexplicable without the hypothesis of quantization."…”
Section: (Quasi-)historymentioning
confidence: 99%
“…Salah satu cabang IPA adalah fisika. Fisika merupakan salah satu mata pelajaran mencakup materi serta perhitungan yang bagi sebagian besar peserta didik dirasa sulit dipahami (Nisa' 2014;Passon, Zügge, and Grebe-Ellis 2019). Seorang guru dituntut memacu peserta didik agar tertarik dalam tiap materi fisika yang diajarkan sehingga peserta didik dapat mengikuti tiap materi serta berpartisipasi aktif dalam pembelajaran.…”
Section: Pendahuluanunclassified
“…Bir diğer önemli nokta modern fizik; fiziği 'bitmiş' olarak değil, devam eden bir süreç olarak sunmaktadır (Passon, Zügge ve Grebe-Ellis, 2019). Toplumların teknolojide birçok gelişmeye ilham veren ve vermeye de devam edecek olan bu alan uzun zamandır ilgi çeken konulardandır (Swinbank, 1992).…”
Section: Introductionunclassified